2014
DOI: 10.3390/nu6125871
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Resveratrol Supplementation on Bone Growth in Young Rats and Microarchitecture and Remodeling in Ageing Rats

Abstract: Osteoporosis is a highly prevalent skeletal disorder in the elderly that causes serious bone fractures. Peak bone mass achieved at adolescence has been shown to predict bone mass and osteoporosis related risk fracture later in life. Resveratrol, a natural polyphenol compound, may have the potential to promote bone formation and reduce bone resorption. However, it is unclear whether it can aid bone growth and bone mass accumulation during rapid growth and modulate bone metabolism during ageing. Using rat models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 59 publications
3
32
0
Order By: Relevance
“…Further, we cannot exclude a possible interactive effect of HF and RSV on bone health, due to the absence of a CON‐RSV group. However, our data are supported by previous reports in both aging and physically inactive male rats that also demonstrated deleterious effects of RSV (12.5–20 mg/kg/day) on tibial bone microarchitecture, mineral mass, and strength—in the absence of an HF challenge. Although not all models respond similarly to RSV, as female ovariectomized (OVX) mice display protective effects of RSV (∼80mg/kg/day) on bone health , our data demonstrate a detrimental effect of RSV in male mice challenged with an HF diet.…”
Section: Discussionsupporting
confidence: 91%
“…Further, we cannot exclude a possible interactive effect of HF and RSV on bone health, due to the absence of a CON‐RSV group. However, our data are supported by previous reports in both aging and physically inactive male rats that also demonstrated deleterious effects of RSV (12.5–20 mg/kg/day) on tibial bone microarchitecture, mineral mass, and strength—in the absence of an HF challenge. Although not all models respond similarly to RSV, as female ovariectomized (OVX) mice display protective effects of RSV (∼80mg/kg/day) on bone health , our data demonstrate a detrimental effect of RSV in male mice challenged with an HF diet.…”
Section: Discussionsupporting
confidence: 91%
“…All serum samples were run in a single assay with the provided standards following instructions provided by the manufacturers. Serum bone formation marker alkaline phosphatase (ALP) levels were performed and analysed on a Konelab™ 20XT Clinical Chemistry Analyzer (Thermo Scientific, Vantaa, Finland) using Thermo Scientific reagents [16].…”
Section: Biochemical Assays For Serum Levels Of Estrogen and Bone Turmentioning
confidence: 99%
“…In particular, resveratrol is reported to be associated with bone protection and bone formation through its action against osteoporosis and bone resorption associated with aging. In addition, it inhibits bone loss associated with estrogen deficiency in resveratrol‐treated animal models . Recent studies have shown that the antioxidant and anti‐inflammatory properties of resveratrol inhibit the inflammatory response of periodontal tissues and prevent alveolar bone loss in rat models caused by bacterial inflammation .…”
Section: Introductionmentioning
confidence: 99%